MORPHOMETRIC ANALYSIS OF CORONARY ARTERIES IN HARYANVI POPULATION - Asar, Vishal; Singh, Kamal; Sharma, Luv; Rohilla, Aarti (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The present study aimed to record the length of coronary arteries was carried out for better anatomical knowledge about the branches of coronary arteries and its variation is essential for cardiologists and interpretation of coronary angiograms by radiologists. Methods: The study group was comprised 60 human cadaveric hearts retrieved from the dead bodies of the age group 18–50 years brought for medicolegal autopsy. Results: In 60 heart specimen’s length of right coronary artery (RCA)-I (34.4–128.8 mm, 81.5±18.1), RCA-II (6.2–43.4 mm, 20.3±9.9), RCA-III (9.6–69 mm, 38.2±18.7), length of left coronary artery (3.4–19 mm, 12.6±3.74 mm), length of left circumflex artery (31.9–144.5 mm, 79.2±26.2 mm), and length of left anterior descending artery (33.4–154.4 mm, 105.3±27 mm). Conclusion: The name and nature of a coronary artery or a branch define that vessel’s vascularization pattern or territory, rather than its origin. Better anatomical knowledge about the branches of the coronary artery and its variation is essential for cardiologists and interpretation of coronary angiograms by radiologists.